Psychosocial Risk in Work Cooperative Partners: Background for the Discussion of Occupational Health - Rubilar-Maturana, C; Inostroza-Rebolledo, P (UNIV JAEN, SERV PUBLICACIONES, 2021)
The work is one of life s most relevant human activities, it has an impact on individuals and organizations. Countries have been encouraged from international agencies to take cover not only from physical security but also at the psychosocial level of workers. In Chile, since 2013, the Protocol on the Surveillance of Psychosocial Risk at work has been implemented for the different labor organizations. In this article realizes the psychosocial risk of worker partners in six worker cooperatives, in a mixed study, it is observed that the results at the quantitative level of organizations get in 4 of the 5 dimensions a low risk (psychological requirements, active work, social support in the company and compensation), while in the double presence dimension they get a high level of risk. Linking the results to the qualitative analysis provides backgrounds the help us understand cooperative management practices would be compensative influencing other psychosocial risks present.